The Kuwaiti Constitution and the Qatari Constitution from formal and substantive aspects - Othman Jazaa Al-Suwaileh, (International Journal of Law Research and Studies, 2025)
This comparative analytical research addresses an aspect of constitutional law for the State of Kuwait and the State of Qatar, highlighting the negatives and positives of the provisions of these two constitutions. First, in the first section, we cover some history of the constitutional documents of both countries, giving the reader a historical overview before delving into the core subject of the research. Continuing in the second section, we discuss the current documents and their formal characteristics, explaining the method of establishing the constitution, the rigidity and flexibility of the constitution, and the number of documents it contains. In the third section, after clarifying some history of the constitutional documents of both countries, and after understanding the characteristics of the current constitution, we explore their differences and similarities to provide the reader with a comprehensive picture of the history of both countries’ documents, the characteristics of the current constitution, and the main formal differences between them. This prepares the reader for the next three sections, where we will reach the core of this research through objective rather than formal comparisons, allowing for a broad understanding and awareness of what will be in the three established sections. In the fourth section, we open the second chapter of the constitution – the topics of all chapters in the Kuwaiti Constitution and the Qatari Constitution are similar – in this chapter, the constitutional articles addressed the rules of society for the state and its basic components that the state must observe. We presented the most different articles, offering an article with a negative aspect from one of the constitutions, and corresponding it with a positive article from the other constitution that addresses this negative aspect, while considering the subjects of both articles and also the other comparisons. The fifth section is the fourth chapter, in which the constitutional articles established provisions for public authorities – executive, legislative, and judicial – and their powers and obligations that must be observed. We presented some negative texts and their flaws, and compared them with positive texts that eliminate these undesirable flaws in the constitutional provisions. The sixth and final section of this research is considered one of the most important topics of research and topics of applying or suspending constitutional articles. We explained the valid justification through which it is permissible to temporarily suspend the application of constitutional articles until the reasons upon which this justification was built are removed. In conclusion, the summary is not sufficient and does not replace opening the pages of the research. The summary is only a tool to know what topics will be addressed in the research.
Keywords: Kuwaiti Constitution; Qatari Constitution; Constitutional System; Comparison of Legislation